Understanding and Overcoming Immunotherapy Resistance in Skin Cancer: Mechanisms and Strategies - Shreya Singh Beniwal; Abhimanyu Chiraparambil Radhakrishnan; Ayanchetty Haripraba; Saif Syed; Gajawada Pragna; Ayush Dwivedi; Akash Rawat; Daniela Castro Calderón; Martin Cevallos‐Cueva (Aging and Cancer)
ABSTRACT Background Immunotherapy that includes immune checkpoint inhibitors (ICI) is a revolutionary arm of the treatment of skin cancers like melanoma, basal cell carcinoma, and squamous cell carcinoma. Despite this leap in clinical advances, a critically challenging area in this field is emerging resistance to immunotherapy that limits its efficaciousness in a profound segment of the population. This resistance can be classified as primary resistance, in which cancers fail to respond to initial regimen, or acquired resistance that develops after there is a favorable initial response. A comprehensive understanding of the basic mechanisms and figuring out novel strategies to combat resistance are necessary to improve patient outcomes. Methods A comprehensive review of recent studies was conducted with focus on preclinical and clinical evidence related to immunotherapy resistance in skin cancer with a wide literature search on databases such as PubMed, Cochrane, and Google Scholar with keywords, including “skin cancer,” “immunotherapy,” “malignant melanoma,” “drug resistance,” “mechanisms,” and “strategies” published in the last 15 years. Results This study aims to establish a review of the molecular and cellular mechanisms that contribute to development of drug resistance in skin cancer and to gauge emerging strategies to overcome these barriers. Insights into these mechanisms were classified into tumor‐intrinsic factors, like genetic and epigenetic changes, and tumor‐extrinsic factors, such as changes in tumor microenvironment (TME) and systemic immunosuppression. Therapeutic strategies that included combination therapies, newer checkpoint inhibitors, and modulation of the TME were evaluated. Key mechanisms leading to drug resistance identified include tumor‐intrinsic factors, including mutations in signaling pathways, tumor‐extrinsic factors, including immunosuppressive cells and changes in the TME, such as hypoxia that contributed to drug resistance. Upcoming strategies to counteract resistance included combination approaches, adoptive T‐cell therapy, and newer immunomodulatory agents that target resistance pathways. Conclusions There is a complex interplay of cancer and immune microenvironmental mechanisms that leads to development of immunotherapy resistance in skin tumor patients. A multi‐pronged approach with focus in fields of genomics and immunology as well as bioinformatics is required, along with combination therapies and novel immunomodulators, to tackle resistance and enhance clinical outcomes for patients suffering with skin tumors.